Essential elements for learning to eat: guidance to support families with infants and young children - Wendy Sue Swanson; Erin Sundseth Ross; Luz Adriana Matiz; Laura Czerkies; Lyndsey R. Huss; Sarah Smith-Simpson; Jodi Bettler; Susan Pac (Frontiers in Pediatrics)
Feeding infants and young children (IYC) is an emotional commitment for caregivers as they strive to achieve a sense of mastery, goodness, and accomplishment in providing nourishment for their children. Feeding practices are important during early childhood for lifelong health and well-being as behaviors related to healthy eating are established, and there is an interrelation between growth, gross/fine motor skills, and social-emotional behavior in shaping “learning to eat” for IYC. Mealtimes and feedings are opportunities for engagement with the family, formation of healthy habits, exposure to different foods, practicing eating skills, and learning to appreciate foods. The caregivers' role is pertinent as they influence and teach children “what” and “how” to eat and play a crucial role in supporting children's social, emotional, and cognitive development in relation to food and mealtimes. This mini review provides practical guidance for caregivers as their IYC “learn to eat.” Caregiver behaviors have changed, particularly in the choice of feeding methods, requiring an update on complementary feeding advice. Healthcare providers can encourage positive feeding practices. Family mealtimes provide opportunities for (1) bonding, (2) practicing and refining gross/fine motor, cognitive, language, and social-emotional skills, (3) offering a variety of nutrient-dense, appropriate textured foods, and (4) reinforcing the central role of the caregiver in establishing healthy eating patterns, a positive relationship with food, and joyful eating experiences. Healthcare providers play a pivotal role in raising awareness among caregivers about the importance of their role in feeding their child(ren).